2013
DOI: 10.1007/s00464-013-3199-6
|View full text |Cite
|
Sign up to set email alerts
|

Construct and concurrent validity of a Nintendo Wii video game made for training basic laparoscopic skills

Abstract: The prototype setup of the Wii Laparoscopy possesses solid construct and concurrent validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…3,16,17 To make sure all questions were understood, this questionnaire has previously been tested on the group of experienced surgeons of our construct and concurrent validity study. 15 (These data are unpublished.) Besides closed questions on the importance of simulation in general and Underground as a training tool compared other simulators, 1 to 10 visual analog scale scores (1 5 lowest score, 10 5 highest score) with questions on the authenticity of the controls, possible usefulness in training, and the lack of haptics and real anatomy were used to assess the opinion of the participants.…”
Section: Assessmentmentioning
confidence: 90%
See 1 more Smart Citation
“…3,16,17 To make sure all questions were understood, this questionnaire has previously been tested on the group of experienced surgeons of our construct and concurrent validity study. 15 (These data are unpublished.) Besides closed questions on the importance of simulation in general and Underground as a training tool compared other simulators, 1 to 10 visual analog scale scores (1 5 lowest score, 10 5 highest score) with questions on the authenticity of the controls, possible usefulness in training, and the lack of haptics and real anatomy were used to assess the opinion of the participants.…”
Section: Assessmentmentioning
confidence: 90%
“…Previous research on the test validity of Underground showed solid construct and concurrent validity. 15 In this study, we showed that experienced laparoscopic surgeons (n 5 15) were significantly faster with a special test level of the game than a control group (internists, n 5 15) (construct validity). These scores were compared with their FLS peg transfer test scores, which showed a significant and high correlation of r 5 .812 (concurrent validity).…”
Section: Goals and Hypothesismentioning
confidence: 91%
“…With the opportunity of simulating MIS, we aim to start training outside of the operating room. Laparoscopic skills such as access, dissection, suturing, knot-tying, precision cutting, haemostasis and reconstruction are initially best acquired in a ''skills-laboratory'' environment, thus improving skills by practice [8,9]. There are also artificial models to simulate specific pathologies, such as esophageal atresia or pielo-ureteric junction obstruction (PUJO), to reproduce and simulate the single steps of specific interventions [10].…”
Section: Discussionmentioning
confidence: 99%
“…This way, the player can play a video game using the same movements as made during laparoscopic surgery. The hardware has already shown to possess solid face, construct, and concurrent validity [18]. However, experimental validity-the actual effect of the game on one's basic laparoscopic skills-has not yet been studied.…”
mentioning
confidence: 99%